Methanolic Leaf Extracts of Certain Plants as Larvicides against Teak skeletonizer, Eutectona machaeralis - Maddala, Madhavi; Lingakari, Mahesh; Bandi, Srikanth (Asian Journal of Biological and Life Sciences)
Aim: The coveted Indian hardwood teak (Tectona grandis) grows well in particular tropical temperatures and soil types. With 8.9 million hectares, India's teak forests are essential to the luxury market. Indian teak trees are seriously threatened by the teak skeletonizer (Eutectona machaeralis Walker), which causes extensive defoliation. As a result, less timber is produced and trees grow slower. Materials and Methods: In this work, methanolic leaf extracts of Wrightia tinctoria, Murraya koenigii and Prosopis juliflora were tested for their larvicidal efficacy against the fourth instar larvae of E. machaeralis. Results: All extracts had high levels of alkaloids, flavonoids and polyphenols, according to phytochemical analyses. The findings showed that mortality rates were concentration-dependent. M. koenigii had the maximum effectiveness, with mortality rates of 61.43±1.76% at 200 ppm and 92.86±2.40% at 400 ppm. Conclusion: These results highlight the potential of these plant extracts as efficient, environmentally beneficial teak pest management options.
Keywords: Eutectona machaeralis; Larvicidal activity; Murraya koenigii; Prosopis juliflora; Teak leaf skeletonizer; Tectona grandis; Wrightia tinctoria